Self-Regulated Learning Strategies in Teenage Writers: A Focus on Self-Assessment and Feedback - Cangkat, Stephanie Rosalina; Setiawan, Slamet; Anam, Syafi'ul (MATAI: International Journal of Language Education, 2025)
Adolescent learners often face significant challenges when developing writing skills in a second language, as they must navigate both linguistic complexity and cognitive demands. This study examines how secondary school students in Indonesia engage in self-regulated learning within English writing tasks, focusing on their use of planning, self-assessment, and response to teacher feedback. Using a qualitative approach, the research involved journal reflections, interviews, and analysis of students’ written work. The findings reveal that while students are beginning to demonstrate self-regulatory behaviors such as setting goals, monitoring their progress, and revising based on feedback their ability to do so independently remains limited. Most learners benefited substantially from scaffolding and teacher support, especially in language accuracy and idea development. Feedback was a powerful catalyst for revision, helping students become more aware of their writing choices and areas for improvement. However, gaps in metacognitive skills and feedback literacy were evident, highlighting the need for more explicit instruction in self-assessment and reflective practice. This study advances our understanding of how self-regulation unfolds in teenage writers and emphasizes the importance of integrating structured reflective tools and responsive feedback into writing pedagogy. By fostering these practices, educators can support the growth of autonomous, engaged learners capable of managing their own learning and improving their writing performance over time.